Apego y dependencia emocional. - Contento Torres, Coraima Laura (2015)
The objective of this research is to determine the characteristics of emotional dependency, as a result of insecure attachment. The basic concepts used were on attachment theory has provided fundamental concepts to explain human relations, during the different stages of the life cycle. Attachment or link is established with the mother will be critical to the emotional and cognitive development. When the attachment figure did not establish a secure link with the child that is where there are imbalances in the later stages of building a kind of insecure attachment of these unfavorable aspects it is the wrong expression in relationships, resulting in emotional dependence. The methodology was qualitative job that allowed describing the characteristics of this work, through the interview and test of emotional dependence. The results confirm the importance of the provision and quality of the mother in the child early because this relationship you have had with their attachment figure will greatly influence and determine the type of attachment. However in this case we could evidence and concluded that the subject has a kind of ambivalent attachment, which makes it in its later stages as a factor of the same emotional dependency is built and that is where the person meets the unmet needs of their childhood. The results suggest the interest of deepening about addiction and know it, because it is of vital importance for the development of the child, in the sense of security, self-esteem and assertiveness to face the world.